First‐trimester screening for trisomies in pregnancies with vanishing twin. (13th February 2020) - Chaveeva, P.; Wright, A.; Syngelaki, A.; Konstantinidou, L.; Wright, D.; Nicolaides, K. H.
ABSTRACT: Objectives: To examine multiples of the median (MoM) values of serum free beta‐human chorionic gonadotropin ( β ‐hCG) and pregnancy‐associated plasma protein‐A (PAPP‐A) in a large series of pregnancies with a vanishing twin, determine the association of these values with the interval between embryonic death and blood sampling, and develop a model that would allow incorporation of these metabolites in first‐trimester combined screening for trisomy. Methods: This was a retrospective study comparing maternal serum free β ‐hCG and PAPP‐A levels at 11–13 weeks' gestation in 528 dichorionic pregnancies with a vanishing twin, including 194 (36.7%) with an empty gestational sac and 334 (63.3%) with a dead embryo, with those in 5280 normal singleton pregnancies matched for method of conception and date of examination. In vanishing‐twin pregnancies with a dead embryo, marker levels were examined in relation to the estimated time between embryonic death and maternal blood sampling. Results: First, in pregnancies with a vanishing twin, median free β ‐hCG MoM was not significantly different from that in normal singleton pregnancies (1.000; 95% CI, 0.985–1.016 vs 0.995; 95% CI, 0.948–1.044; P = 0.849). Second, PAPP‐A MoM was higher in vanishing‐twin pregnancies than in normal singleton pregnancies (1.000; 95% CI, 0.985–1.015), both in the group with an empty gestational sac (1.165; 95% CI, 1.080–1.256; P = 0.0001) and in that with a dead embryo (1.175; 95% CI, 1.105–1.249; P < 0.0001). Third, in vanishing‐twin pregnancies with a dead embryo, PAPP‐A MoM was related inversely to the interval between estimated gestational age at embryonic demise and blood sampling ( P < 0.0001). Fourth, in first‐trimester screening for trisomy 21 in singleton pregnancies, the estimated detection rate, at a 5% false‐positive rate, was 82% in screening by a combination of maternal age and fetal nuchal translucency thickness, and this increased to 86% with the addition of serum free β ‐hCG and to 91% with the addition of serum PAPP‐A. Fifth, similar performance of screening can be achieved in pregnancies with a vanishing twin, provided the appropriate adjustments are made to the level of PAPP‐A for the interval between estimated gestational age at embryonic demise and blood sampling. Conclusions: First‐trimester screening for trisomy in pregnancies with a vanishing twin should rely on a combination of maternal age, fetal nuchal translucency thickness and serum free β ‐hCG, as in singleton pregnancy, without the use of serum PAPP‐A. Alternatively, PAPP‐A can be included but only after appropriate adjustment for the interval between estimated gestational age at fetal demise and blood sampling. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.